Opioid Prescribing Habits for Common Arthroscopic Procedures in Opioid Naïve Patients - Thompson, Matthew M. (Orthop J Sports Med, 2021)
BACKGROUND: With the opioid epidemic and the increasing number of opioid-related deaths, there is growing awareness in the medical community regarding the dangers of opioid overprescription. As a result, there is a willingness among physicians to abandon old norms and adopt new data-driven prescribing practices. PURPOSE: To demonstrate patient-reported consumption data of opioid medications after anterior cruciate ligament (ACL) reconstructions (ACLRs), knee arthroscopies, and rotator cuff repairs to provide data-driven guidelines for prescribing opioids after these procedures. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Included in the study were 168 patients who underwent an ACLR, knee arthroscopy, or arthroscopic rotator cuff repair over a 17-month period. Patients were excluded if they had an opioid allergy, had preexisting opioid use, had an acute postoperative complication requiring further surgery, required hospitalization, exhibited drug-seeking behaviors, or were lost to follow-up. Medical records were reviewed to determine the number of opioid pills prescribed and the number of pills taken postoperatively. Prescribing was standardized in that 15 hydrocodone/acetaminophen pills (5/325 mg) were prescribed for all knee arthroscopy procedures and 40 hydrocodone/acetaminophen pills were prescribed for all ACL and rotator cuff procedures. The mean number of pills consumed and percentage of prescribed pills taken were analyzed in association with specific procedures and patient demographics. RESULTS: Overall, the mean (±SD) reported opioid consumption overall was 13.5 ± 13.0 pills, with a utilization rate of 45.6% of the prescription. The mean reported opioid consumption for ACLRs, knee arthroscopies, and rotator cuff repairs was 19.1 ± 15.4, 7.2 ± 5.4, and 17.2 ± 14.3 pills, respectively (P < .001). This represented a utilization rate of 48%, 47%, and 41%, respectively. CONCLUSION: This study provides important information regarding opioid utilization after common arthroscopic procedures. For ACLRs, knee arthroscopies, and rotator cuff repairs, by respectively prescribing 20, 10, and 20 pills postoperatively, the amount of unused medications would decrease by 60%, 47%, and 64%, respectively. We recommend prescribing no more than 20, 10, and 20 hydrocodone/acetaminophen pills (5/325 mg) for ACLRs, knee arthroscopies, and arthroscopic rotator cuff repairs, respectively.